2017
DOI: 10.1016/j.jaac.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Euthymic Pediatric Bipolar Disorder: A Systematic Review and Meta-Analysis

Abstract: Euthymic youths with BD exhibit significant cognitive dysfunction encompassing verbal learning and memory, working memory, and/or visual learning and memory domains. These data indicate that for a subset of individuals with BD, neurodevelopmental factors may contribute to cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 77 publications
2
40
0
1
Order By: Relevance
“…28 In contrast, a subsequent meta-analysis focussing on studies of euthymic BD youth exclusively, found impairments only in the domains of verbal and visual memory/learning as well as working memory compared to healthy controls. 29 While memory deficits are consistent with that of euthymic adult BD samples, the absence of processing speed, reasoning and problem-solving, and attention/vigilance deficits that are commonly seen in euthymic BD adults suggests a less pervasive trait-like dysfunction in younger onset patients. Interestingly, the one study of longitudinal cognitive changes in PBD 30 found impairments in most cognitive domains in predominantly euthymic patients ranging in age between 9 and 14 years.…”
Section: Post-onset Cognitive Functioning In Paediatric First Epismentioning
confidence: 65%
See 1 more Smart Citation
“…28 In contrast, a subsequent meta-analysis focussing on studies of euthymic BD youth exclusively, found impairments only in the domains of verbal and visual memory/learning as well as working memory compared to healthy controls. 29 While memory deficits are consistent with that of euthymic adult BD samples, the absence of processing speed, reasoning and problem-solving, and attention/vigilance deficits that are commonly seen in euthymic BD adults suggests a less pervasive trait-like dysfunction in younger onset patients. Interestingly, the one study of longitudinal cognitive changes in PBD 30 found impairments in most cognitive domains in predominantly euthymic patients ranging in age between 9 and 14 years.…”
Section: Post-onset Cognitive Functioning In Paediatric First Epismentioning
confidence: 65%
“…An initial meta‐analysis of 12 studies of BD youth across several mood states showed widespread, medium effect size deficits in cognition generally, and in most individual domains . In contrast, a subsequent meta‐analysis focussing on studies of euthymic BD youth exclusively, found impairments only in the domains of verbal and visual memory/learning as well as working memory compared to healthy controls . While memory deficits are consistent with that of euthymic adult BD samples, the absence of processing speed, reasoning and problem‐solving, and attention/vigilance deficits that are commonly seen in euthymic BD adults suggests a less pervasive trait‐like dysfunction in younger onset patients.…”
Section: Trajectory Of Cognitive Functioning In Bdmentioning
confidence: 97%
“…The presence of cognitive impairments among subjects affected by Bipolar Disorder (BD) in comparison to healthy individuals has been attested by several studies (Mann-Wrobel et al, 2011), especially in executive functioning, attention, visual/motor processing speed, verbal memory and verbal learning (Torres et al, 2007;Van Der Werf-Eldering et al, 2011). Interestingly, neurocognitive deficits seem to represent a trait feature of BD since cognitive alterations have been detected during all phases of the illness (Cipriani et al, 2017;Martínez-Arán et al, 2000), even during euthymia (Bostock et al, 2017;Elias et al, 2017).…”
Section: Main Textmentioning
confidence: 99%
“…However, the effect of AD on early‐onset bipolar disorder is less known and current studies usually have the limitation of small sample sizes. In PBD patients, anxiety comorbidity explains some of the heterogeneity observed in attention and working memory . PBD patients with AD comorbidity have more severe impairment and are admitted to the hospital more often .…”
Section: Introductionmentioning
confidence: 99%